Application Of Canvas Model Business Analysis: Case Study Of Free Power Business - Diki Ramadani; Joko Susanto; Riska Apri Arianti (JASc (Journal of Agribusiness Sciences), 2019)
One of the technological tools that can not be separated from people's lives is cellphones, but the consequences of increasingly sophisticated technological tools are the higher power requirements. Current technology has developed into portable tools, namely tools that do not need to be connected directly to the main source of electric current but use the power stored in the battery, FREE POWER is a business that is engaged in Powerbank, where the product of the power source Free Power utilizes magnetic energy generator that can be used continuously without having to worry about running out of power. The types and sources of data used in this study are qualitative, the data needed in this study are primary data and secondary data. FREE POWER in the form of an innovative charging device on a smartphone by utilizing a magnetic generator that has the advantage of being able to charge continuously without having to recharge. With a cheaper price compared to a power bank. FREE POWER is the right solution to support the smooth use of the smartphone itself, so that the operation is not constrained due to the depletion of the smartphone battery used. And for consumers themselves are intended for teenagers to adults.